Income elasticity of child labor: Do cash transfers have an impact on the poorest children? - Luca Pellerano; Eleonora Porreca; Furio Camillo Rosati (IZA Journal of Development and Migration, 2020)
The possible nonlinearity of the income elasticity of child labor has been at the center of the debate regarding both its causes and the policy instruments to address it. We contribute to this debate providing theoretical and empirical novel results. From a theoretical point of view, for any given transfer size, there is a critical level of household income below which an increase in income has no impact on child labor and education. We estimate the causal impact of an increase in income on child labor and education exploiting the random allocation of the Child Grant Programme, an unconditional cash transfer (CT), in Lesotho. We show that the poorest households do not increase investment in children's human capital, while relatively less poor households reduce child labor and increase education. In policy terms, the results indicate that CTs might not be always effective to support the investment in children's human capital of the poorest households. Beside the integration with other measures, making the amount of transfer depends of the level of deprivation of the household, might improve CT effectiveness.
Keywords: H; C93; I28; J1; J24; 330; child labor; education; cash transfer; randomized experiment; Lesotho